The Thought of Ibn Rushd : Science and Religion - Ahmad Fatoni; Maya Fitriyatul Farida (Edumaspul: Jurnal Pendidikan, 2024)
In Ibn Rushd's view, philosophy and religion occupy the main position and are comparable in the theory of knowledge (epistemology), both of which are positioned as subjects in seeing things. This is what is then called, the relationship between religion and philosophy. Then Ibn Rushd came to the conclusion, philosophizing is something that is required or recommended in sharia. Ibn Rushd has the real name Abu al-Walid Muhammad Ibn Ahmad Ibn Muhammad Ibn Rushd was born in Cordoba in 520 AH or 1126 AD. He died on 9 Safar, 595 H or December 11, 1198 AD at the age of 72. Ibn Rushd thought that true science is knowledge and recognition (ma'rifat) of Allah and knowledge of all His creations in accordance with the truth, in accordance with their characteristics, in accordance with their specialty, knowledge of science for the happiness of the hereafter. According to ibnu rusyd, science is considered a true science if it has reached the stage of recognition of Allah SWT and all His creations. So this true knowledge is the main goal of sharia which of course must also be accompanied by the correct practice. No form of thought that developed in his time escaped his criticism and analysis, a criticism built on established rationality. The emergence of Ibn Rushd's thought was like a "shock" to the status quo. Besides shouting the opening of the door to ijtihad in all fields, he also tried to rationalize all forms of science in his time.